2020
DOI: 10.3390/diagnostics10100809
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Predictors of Nonalcoholic Fatty Liver Disease among Type 2 Diabetes Mellitus Patients at Primary Health Care Level in South Western Saudi Arabia

Abstract: Objectives: To predict the role of different clinical and biochemical parameters in identifying nonalcoholic fatty liver disease (NAFLD) among patients with type 2 diabetes mellitus (T2DM) in Abha city, southwestern Saudi Arabia. Methods: A stratified random sample was selected. A detailed clinical and biochemical examinations were performed. Using portable abdominal ultrasound examination, NAFLD was identified. The study used receiver operating characteristic (ROC) analysis. Results: The study covered 237 T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Similar observations were also obtained by a study among Montenegrin population, found that ALT was independent predictor for NAFLD but with a higher cutoff point of 22 IU/L [24]. These results are also consistent with that of Al Humayed et al [25] who identified that ALT is a predictor for NAFLD with a threshold cutoff value of 22.1 nmol/L. Our lower ALT cutoff point might be explained by that the present study was done among individuals without diabetes while the participants of other studies had diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations were also obtained by a study among Montenegrin population, found that ALT was independent predictor for NAFLD but with a higher cutoff point of 22 IU/L [24]. These results are also consistent with that of Al Humayed et al [25] who identified that ALT is a predictor for NAFLD with a threshold cutoff value of 22.1 nmol/L. Our lower ALT cutoff point might be explained by that the present study was done among individuals without diabetes while the participants of other studies had diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…In clinical, NAFLD patients are more likely to suffer from metabolic syndrome, such as obesity, insulin resistance, type 2 diabetes mellitus (T2DM), dyslipidemia, and hypertension [ 5 , 6 ]. Among these complications, T2DM seems to be the essential clinical predictor of adverse clinical reactions, such as advanced liver fibrosis and mortality in NAFLD patients [ 7 , 8 ]. A systematic review and meta-analysis reported that, among T2DM patients, the global prevalence of NAFLD and NASH was 55.5% and 37.3%, respectively, and about 17.0% advanced fibrosis in patients with NAFLD and T2DM [ 9 ].…”
Section: Introductionmentioning
confidence: 99%